COMMUNICATION RELATIONS AND WORK FACILITIES ON THE PERFORMANCE OF OFFICE EMPLOYEES CIANGSANA VILLAGE BOGOR - Nurdin; Suzanna Josephine Tobing; Ktut Silvanita (Fundamental Management Journal, 2023)
The building blocks of an organization's sustainability are its human resources. The art and dynamic of managing energy for outcomes that advance an organization exist. In this instance, human resources have an impact on an organization's success. Employees play a crucial role in helping the firm achieve its objectives as resources or labor. The methodology is quantitative in nature. This is based on statistical analysis and the gathering of data using a particular population as the research instrument. The quantitative method aims to test the established hypothesis, this type of research is a case study by collecting data through giving a list of questions (questionnaires) to respondents. db) n-2 28 for two-way test is 2048. Based on the above calculation, it is obtained that t arithmetic (4.084) is greater than t table (2.048) and the value of sig (0.000) is less than 0.05, then Ho is rejected and Ha is accepted, which means there is a significant relationship between communication and employee performance. then t table at a significant level of 0.05, the number of samples (n) 30, and degrees of freedom (db) n-2 28 for two-way testing is 2,048. Based on the above calculation, it is obtained that t count (3.826) is greater than t table (2.048) and the value of sig (0.000) is less than 0.05, then Ho is rejected and Ha is accepted which means there is a significant relationship between work facilities and the performance of employees who work in doing his job. To improve employee performance, the leadership should always provide information that can be understood by employees and evaluations are always carried out on a scale. To improve employee performance, the sub-district office should be able to provide instructions for the operation of the facility so as to make it easier for its users and the available communication facilities and equipment tailored to their needs. In addition, it is necessary to provide adequate rest rooms for employees. Keywords: Communication, Work Facilities, Employee Performance